Gliwiczia gen. nov. a new monoraphid diatom genus from Lake Baikal with a description of four species new for science - Kulikovskiy, Maxim; Lange-Bertalot, Horst; Witkowski, Andrzej (Phytotaxa, 2013)
This paper proposes a new monoraphid genus Gliwiczia Kulikovskiy, Lange-Bertalot & Witkowski, separated from Achnanthes sensu lato. Here we describe four species G. skvortzowii Kulikovskiy, Lange-Bertalot & Witkowski, G. tenuis Kulikovskiy, Lange-Bertalot & Witkowski, G. latarea Kulikovskiy, Lange-Bertalot & Witkowski and G. vixcalcar Kulikovskiy, Lange-Bertalot & Witkowski which all are new to science. In terms of morphology, this group of species closely resembles Achnanthes calcar Cleve. Also proposed is the taxonomic transfer of A. calcar Cleve to Gliwiczia calcar (Cleve) Kulikovskiy, Lange-Bertalot & Witkowski comb. nov. Our taxonomic conclusions about the position of this group of species is based on light microscopic (LM) examination of the type material of A. calcar and on extensive LM and scanning electron microscopic (SEM) studies on material originating from Lake Baikal. This new genus differs from other established monoraphid genera in the of cavum (horse shoe) present on both raphe and sternums valves, uniseriate striae on both valves, and areola occlusions in a form of open circular foramina externally. The raphe valve is only slightly concave, whereas the sternum valves appear flat. Only one of the species belonging in Gliwiczia gen. nov., G. calcar, is known to inhabit oligotrophic and dystrophic freshwater lakes of Eurasia. It seems highly likely that the newly described species are limited in their distribution to the waters of Lake Baikal. None of them have thus far been illustrated in any accessible literature even under provisional names.